(untitled) (Philologia, 2021)
The arrival and settlement in Britain since 1945 of new immigrant communities has introduced fresh themes, formal structures and narrative subjects into British fiction. Many of these novels, written by second and third generation immigrants, concern the process of departure, transition and adjustment arising from the experience of coming to a new country. Zadie Smith’s White Teeth and Monica Ali’s Brick Lane are two such novels, representing different aspects of the immigrant experience, the first from the Caribbean and the second from Bangladesh. Their narrative modes and points of view are very different and demonstrate contrasting approaches to the representation of change and the challenges, tensions and complexities of Britain rapidly-changing multicultural society.